A Top‐Down Approach towards Cu(I) Alkynyl Clusters with Unusual Geometry. Issue 4 (29th March 2021) - Li, Huan; Li, Ting; Liu, Shuimiao; Qu, Mei; Liang, Linfeng; Zhang, Fengwei; Zhang, Xian‐Ming
Main observation and conclusion: To search for novel Cu(I) complexes, traditional approaches focus on designing and screening ligands, metal precursors and reaction parameters. In this report, we propose a top‐down approach, in which Cu precursor is first reduced to nanoparticles in the presence of alkynyl and phosphine ligands. The nanoparticles then undergo an auto‐oxidation step in open air to give CuO powder. During this process, a new tetranuclear Cu(I) cluster with an unprecedented centered triangular configuration, [Cu4 (PhC≡C)3 (dppp)3 ]NO3, is isolated in the supernatant. To demonstrate the feasibility of such strategy, it is applied to synthesize another two new Cu(I) clusters, [Cu6 (PhC≡C)5 (dppe)3 ]NO3 and Cu4 (PhC≡C)4 (dpph)2 . The latter has shown a photoluminescence at 511 nm with a quantum yield of as high as 69.84%. Abstract : A top‐down approach has been developed to synthesize three novel alkynyl and phosphine protected Cu clusters from Cu nanoparticles. A peculiar centered triangle Cu4 and a Cu6 uniform triangular prism clusters are discovered by simply using different bidentate phosphine ligands.